Nomenclatural notes on the genus Psoralea (Psoraleeae, Fabaceae) in South Africa - Stirton, Charles H.; Bello, Abubakar; Muasya, A. Muthama (Plant ecology and evolution, 2025)
Background and aims – As part of recent taxonomic studies in the tribe Psoraleeae of Fabaceae, species delimitations and name application have been clarified. This has necessitated some nomenclatural changes to replace illegitimate species names published under Psoralea subgenus Otholobium. Material and methods – We reviewed nomenclature literature, including protologues, and examined type and other specimens both in the field and in herbaria. Herbaria consulted include at BM, BOL, GRA, K, KEI, MEL, MO, NBG, NH, NU, P, PRC, PRE, PRU, S, SAM, STE, TCD, US, and Z. Key results – Six new names are provided: Psoralea acocksii C.H.Stirt. & Muasya (for P. pustulata (C.H Stirt.) C.H.Stirt.); P. albidula C.H.Stirt. & Muasya (for P. parviflora E.Mey.); P. lancifolia C.H.Stirt. & Muasya (for P. lanceolata (C.H.Stirt. & Muasya) C.H.Stirt.); P. psammophila C.H.Stirt. & Muasya (for P. incana (C.H.Stirt.) C.H.Stirt.); P. reticulata C.H.Stirt. & Muasya (for P. carnea E.Mey.); and P. purpurascens C.H.Stirt. & Muasya (for the neglected but legitimate species P. cephalotes Eckl. & Zeyh.). Conclusion – The work further clarifies the application of names in the genus Psoralea . We provide full species descriptions, updated distribution maps, and preliminary conservation status assessments using the IUCN criteria.